Comportamientos de los delitos sexuales cometidos contra adultos en Colombia en el periodo 2016-2020 (2022)
The purpose of the following document is to conduct a descriptive study about sexual crimes in adults, to conduct an analysis and understanding of how their behavior has been in the period from 2016 to 2020 in Colombia. The effects on health due to these events are determined, in which some irregularities in the mental health of the victims are mentioned, as well as behavioral disorders, reproductive health and fatal results. As specific objectives, the behavior of sexual crimes in adults is described, depending on the departments of the country, the behavior of sexual crimes in adults according to gender is explained, in addition to specifying the behavior of crimes sex in adults, depending on the characteristics of the crimes. Vulnerabilities against sexual crimes in adults are exposed in the same way, in which the lack of social recognition towards women, sexual crimes in people with an intellectual disability and the Colombian armed conflict are mentioned. On the other hand, the implications and consequences of this crime, short-term and long-term symptoms, are clearly explained. As well as statistics that also show the detailed figures of the reports made during this period in the different departments and cities of the country.